Recycling process of polyurethane damping material

Through a multi-step polyurethane vibration-absorbing material recycling process, the problem of difficulty in maintaining vibration-absorbing performance in the traditional regeneration process is solved, efficient regeneration and recycling of materials is achieved, and the performance and application value of materials are improved.

CN119775623AActive Publication Date: 2025-04-08DONGGUAN MINGKAI PLASTICS TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510173283.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-08
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

During the recycling and utilization of existing polyurethane vibration-absorbing materials, it is difficult to maintain the vibration-absorbing performance of the regenerated materials. It is mainly because the microstructure is destroyed during the traditional regeneration process, making it difficult to reproduce the original bubble distribution and structure.

Method used

A polyurethane vibration-absorbing material regeneration process is adopted, including pretreatment, ultrasonic dissolution, nano-enhancement, catalytic recombination, foaming and curing forming steps, and the microstructure of the material is reconstructed by finely controlling the conditions and parameters of each step.

Benefits of technology

It effectively maintains the vibration damping performance of recycled materials, improves the quality and application range of materials, and greatly increases the recycling value of polyurethane vibration damping materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775623A_ABST
    Figure CN119775623A_ABST
Patent Text Reader

Abstract

The invention discloses a recycling process of a polyurethane damping material. The recycling process comprises the steps of pretreatment, ultrasonic dissolution, nano reinforcement, catalytic recombination, foaming shaping and curing forming. The method specifically comprises the following steps: crushing the waste material into micron-sized particles in an inert atmosphere; dissolving the particles in an organic solvent and adding a modifier; adding a surface modified graphene nanosheet; a catalytic activity gradient is formed through the bi-component catalyst; a fluorine-containing surfactant is added, and mixed gas is introduced for foaming; and finally, applying an ultrasonic field under temperature gradient and pressure for curing and forming. According to the technical scheme, microstructure formation in the regeneration process can be accurately controlled, and the vibration reduction performance of the regenerated material is effectively maintained and improved. And through the synergistic effect of multiple innovative technologies, high-quality recycling of the waste polyurethane damping material is realized, and a new technical support is provided for circular economy of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane material recycling, in particular to a recycling process of polyurethane vibration damping material. Background Art

[0002] Polyurethane vibration damping material is a high-performance material widely used in industry, transportation and construction. Its unique porous structure and excellent elastic properties enable it to effectively absorb and disperse vibration energy, thereby reducing the impact of noise and vibration on equipment and structures.

[0003] However, the existing recycling process of polyurethane vibration damping materials faces a key technical challenge: it is difficult to maintain the vibration damping performance of the recycled materials. This problem arises from the fact that the performance of polyurethane vibration damping materials is highly dependent on their microstructure, especially the size, distribution and connectivity of the bubbles. In the traditional recycling process, the waste materials are first crushed into small particles and then formed by hot melting and re-foaming. In this process, the original fine bubble structure is destroyed, and during re-foaming, it is difficult to reproduce the microstructure of the original material due to the lack of precise control of the reaction kinetics and the bubble formation process. As a result, the bubbles in the recycled materials are unevenly distributed and inconsistent in size, which seriously affects the vibration damping performance of the material. This not only limits the use of recycled materials in high-demand application fields, but also greatly reduces the recycling value of the materials, becoming a major obstacle to the sustainable development of polyurethane vibration damping materials. Summary of the invention

[0004] The main purpose of the present invention is to solve the technical problem that the vibration reduction performance of the recycled polyurethane vibration reduction material is difficult to maintain during the recycling process of the existing polyurethane vibration reduction material.

[0005] A first aspect of the present invention provides a recycling process for a polyurethane vibration damping material, the recycling process for a polyurethane vibration damping material comprising: 1) Pretreatment step: crush the waste polyurethane vibration damping material into particles of 30-50 microns under the protection of an inert atmosphere; 2) Ultrasonic dissolution step: add the crushed particles into an organic solvent, dissolve them at 50-80°C for 30-60 minutes under the action of 20-60kHz ultrasonic waves, and add 1-5% by mass of an isocyanate modifier at the same time; 3) Nano-enhancement step: adding 0.3-1% by mass of surface-modified amino-functionalized graphene nanosheets to the solution and adjusting the pH value of the solution to 6-7; 4) Catalytic recombination step: first add 0.2-0.5% by mass of a first catalyst to the solution, stir for 10-30 minutes, then add 0.1-0.3% by mass of a second catalyst, wherein the first catalyst is an organic amine catalyst and the second catalyst is an organic tin catalyst, to form a catalytic activity gradient; 5) Foaming and shaping step: add 1-5% by mass of a fluorinated surfactant to the solution, stir intermittently at a speed of 1500-2500 rpm, and introduce a mixed gas of nitrogen and carbon dioxide in a volume ratio of 4:1-5:1; 6) Curing and molding step: the foamed material is cured for 2-6 hours at a temperature gradient of 30-70°C and a pressure of 3-10MPa while applying a 15-35kHz ultrasonic field to obtain a recycled polyurethane vibration damping material.

[0006] Optionally, the preprocessing step specifically includes: The waste polyurethane vibration damping material is embrittled in a low temperature environment of -30 to -40°C for 1 to 2 hours; Under the protection of nitrogen, the first pulverization is carried out at -15 to -25°C, and the obtained particles are kept warm for 5 to 10 minutes and then pulverized for the second time at -5 to -10°C; Through air flow classification, particles with a particle size of 30-50 microns are obtained.

[0007] Optionally, the ultrasonic dissolution step specifically includes: The crushed particles are mixed with an organic solvent in a mass ratio of 1:3-1:8, and precooled at -5 to 5°C for 30-60 minutes; The mixture is placed under 20-60kHz ultrasonic waves, heated to 50-80°C at a rate of 2-5°C / min, and maintained at the heated temperature for 30-60 minutes to dissolve; During the dissolution process, pulsed ultrasound treatment was performed every 15 min for 30–60 s at a frequency of 40–80 kHz; After dissolving for 20-30 minutes, add 1-5% by mass of isocyanate modifier at a rate of 0.5-1 mL / min; After dissolution is completed, rotary evaporate at 80-100°C for 15-25 minutes, and control the evaporation rate to 2-4 mL / min; The solution was cooled to 20-30 °C.

[0008] Optionally, the organic solvent is selected from one or more of dichloromethane, tetrahydrofuran, and N,N-dimethylformamide.

[0009] Optionally, the nano-enhancement step specifically includes: Dispersing 0.3-1% by mass of amino-functionalized graphene nanosheets in N-methylpyrrolidone and ultrasonically treating for 15-30 minutes; Adding 0.5-2% by mass of a silane coupling agent to the dispersion, stirring and reacting at 60-80° C. for 1-2 hours to obtain surface-modified nanosheets; The modified nanosheets are mixed with the solution formed in the ultrasonic dissolution step, and high shear dispersion is performed at a shear rate of 1000-2000 s⁻¹ for 30-60 minutes; Slowly add 0.1-0.3% dopamine by mass, adjust the pH value of the solution to 6-7, and stir at 40-60°C for 2-4 hours; The vacuum degassing treatment was performed at a pressure of 0.1-0.5 MPa for 10-20 minutes.

[0010] Optionally, the modified nanosheets are mixed with the solution formed in the ultrasonic dissolution step, and high shear dispersion is performed at a shear rate of 1000-2000 s⁻¹ for 30-60 minutes, specifically comprising: The modified nanosheets are mixed with the solution formed in the ultrasonic dissolution step at a mass ratio of 1:100-1:500, and premixed at 25-35° C. for 10-20 minutes; The premixed solution is placed in a shearing device and sheared at an initial shear rate of 500-800 s⁻¹ for 5-10 minutes, then the shear rate is gradually increased to 1000-2000 s⁻¹ at a rate of 100-200 s⁻¹ per minute, and the shear rate is maintained for 30-60 minutes; During the high shear dispersion process, pulsed ultrasonic treatment was performed for 20-30 seconds every 10-15 minutes, with an ultrasonic power density of 0.3-0.6 W / cm² and a frequency of 40-60 kHz.

[0011] Optionally, the catalytic recombination step specifically includes: The solution formed in the nano-enhancement step is heated to 45-55° C.; Slowly adding a first catalyst having a mass fraction of 0.2-0.5% at a rate of 0.3-0.7 mL / min; Stir at 45-55°C for 10-30 minutes at a stirring rate of 250-350 rpm; Adding a second catalyst having a mass fraction of 0.1-0.3% dropwise at a rate of 0.2-0.5 mL / min; During the dropwise addition of the second catalyst, the temperature was raised to 65-75° C. at a rate of 1.5-2.5° C. / min; After the second catalyst is added dropwise, stirring is continued at 65-75° C. for 40-70 minutes at a stirring rate of 350-450 rpm; The temperature was lowered to 35-45°C at a rate of 2-4°C / min and allowed to stand at this temperature for 3-5 hours to form a catalytic activity gradient.

[0012] Optionally, the first catalyst is selected from one or more of diazabicyclo[5.4.0]undec-7-ene, triethylenediamine, and N,N-dimethylcyclohexylamine; The second catalyst is selected from one or more of dibutyltin dilaurate, stannous octoate, and dibutyltin dioctoate.

[0013] Optionally, the foaming and shaping step specifically includes: Cooling the solution formed in the catalytic recombination step to 20-25° C.; Slowly adding 1-5% by mass of a fluorinated surfactant to the solution, wherein the fluorinated surfactant is selected from one or more of perfluorooctane sulfonamide, perfluorodecyl sulfonamide, and perfluorododecyl sulfonamide; Use 1500-2500rpm speed for intermittent stirring, stirring for 30-60 seconds each time, with an interval of 60-120 seconds, and repeat 5-8 times; Raise the temperature to 30-35°C at a rate of 1-2°C / min; A mixed gas of nitrogen and carbon dioxide with a volume ratio of 4:1-5:1 is introduced, and the gas flow rate is controlled at 0.5-1L / min; During the aeration process, continuous stirring was performed at 500-800 rpm for 10-15 minutes; The temperature was raised to 40-45°C at a rate of 0.5-1°C / min, while the stirring speed was reduced to 300-500 rpm for 20-30 minutes; Keep the temperature at 40-45°C and let it stand for 30-60 minutes to stabilize the foam structure.

[0014] Optionally, the curing and molding step specifically includes: The material formed in the foaming and shaping step is placed in a mold, the temperature of the bottom of the mold is set to 30° C., and the temperature of the top of the mold is set to 70° C., so as to form a temperature gradient; Apply pressure gradually to 3-10MPa at a rate of 0.5-1MPa / min; During the pressurization process, an ultrasonic field of 15-35kHz is applied simultaneously, with an ultrasonic power density of 0.5-1.5W / cm²; Maintaining the pressure and ultrasonic field for 2-6 hours, wherein the temperature gradient remains unchanged for the first 1-2 hours, and then gradually reducing the temperature of the top of the mold to 50° C. at a rate of 0.5-1° C. / min; After 4-5 hours of curing, reduce the ultrasonic power density to 0.2-0.5W / cm² and continue for 1-2 hours; The pressure is gradually released at a rate of 0.3-0.5 MPa / min, the ultrasonic field is turned off, and the mixture is naturally cooled to room temperature to obtain a regenerated polyurethane vibration damping material.

[0015] The technical solution provided by the embodiments of the present application has at least the following advantages: First, in the pretreatment step, the waste material is crushed into particles of 30-50 microns. This fine crushing process lays the foundation for subsequent dissolution and reconstruction. By controlling the particle size at the micron level, the specific surface area of ​​the material is greatly increased, which is conducive to molecular reorganization and structural reconstruction in subsequent steps. The pretreatment step is carried out under an inert atmosphere, which effectively prevents oxidation or other adverse reactions of the material during the crushing process, ensuring the integrity of the original molecular structure.

[0016] In the ultrasonic dissolution step, the cavitation effect and thermal effect of ultrasound are used to achieve full dissolution of the polyurethane material at the molecular level. When ultrasound propagates in a liquid, tiny bubbles are generated. These bubbles expand and collapse rapidly under high-frequency vibrations, creating a local high temperature and high pressure environment, which helps to break the hydrogen bonds and van der Waals forces between polyurethane molecules and promote the dissolution of the material. At the same time, the addition of isocyanate modifiers can repair some of the molecular chains that have been broken during use, providing a better molecular basis for subsequent reconstruction. The temperature of this step is controlled at 50-80°C, which can not only ensure full dissolution, but also avoid molecular chain degradation caused by excessively high temperatures.

[0017] The nano-enhancement step introduces surface-modified amino-functionalized graphene nanosheets. Graphene can form effective physical cross-linking points in the polyurethane matrix due to its excellent mechanical properties and large specific surface area. Amino functionalization enables graphene to form chemical bonds with polyurethane molecules, further enhancing the overall performance of the material. By adjusting the solution pH to 6-7, the dispersion state of graphene in the polyurethane matrix can be optimized to ensure the uniformity of the nano-enhancement effect.

[0018] The catalytic restructuring step uses a dual catalyst system to form a catalytic activity gradient. The first catalyst (organic amine) mainly promotes the reaction of isocyanate with hydroxyl groups, while the second catalyst (organic tin) is more conducive to the restructuring of polyether or polyester chain segments. This gradient catalytic system can precisely control the reconstruction process of the polyurethane network and help form a microstructure closer to the original material.

[0019] In the foaming and shaping step, a fluorinated surfactant and a gas mixture are used for foaming. Through intermittent stirring and precisely controlled gas introduction, the bubble size and distribution can be finely regulated. This step directly affects the pore structure of the recycled material and is crucial for restoring the original vibration reduction performance. Fluorinated surfactants can significantly reduce the gas-liquid interfacial tension and help form stable small bubbles, while the mixed use of nitrogen and carbon dioxide can adjust the expansion rate and final size of the bubbles.

[0020] Finally, the curing step uses a temperature gradient, pressure control, and ultrasonic field-assisted method. The temperature gradient helps to form a directional polymer chain arrangement, pressure control can adjust the density and porosity of the material, and the application of the ultrasonic field can promote the movement and rearrangement of the molecular chain, which is conducive to the formation of a more uniform and stable network structure. This multi-parameter coordinated control method can accurately regulate the final structure of the material at the molecular level.

[0021] In summary, this solution reconstructs the microstructure of polyurethane vibration damping materials at the molecular level through a series of finely controlled steps. Each step specifically solves the problems in the traditional regeneration process, such as molecular chain breakage, bubble structure destruction, and uneven performance. In this way, the recycled material can be as close to the microstructure of the original material as possible, thereby effectively maintaining its vibration damping performance. This not only improves the quality and application scope of the recycled material, but also greatly increases the recycling value of polyurethane vibration damping materials, providing an effective way to solve obstacles to sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0023] Figure 1 The figure is a flow chart of the recycling process of the polyurethane vibration damping material in the embodiment of the present invention.

[0024] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0027] In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, "and / or" in the full text includes three solutions. Taking A and / or B as an example, it includes technical solution A, technical solution B, and technical solution that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, which must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0028] An embodiment of the present application provides a recycling process of a polyurethane vibration damping material. Figure 1 A flow chart of a recycling process of a polyurethane vibration damping material provided in an embodiment of the present application. In this embodiment, the method includes: See also Figure 1 , Pretreatment step: crush the waste polyurethane vibration damping material into particles of 30-50 microns under the protection of an inert atmosphere; In one embodiment of the present invention, the pretreatment step specifically includes: embrittlement treatment of the waste polyurethane vibration damping material in a low temperature environment of -30 to -40°C for 1-2 hours; under the protection of nitrogen, the first crushing is carried out at -15 to -25°C, the obtained particles are subjected to 5-10 minutes of insulation treatment, and then the second crushing is carried out at -5 to -10°C; and particles with a particle size of 30-50 microns are obtained through air flow classification.

[0029] In specific implementation, the waste polyurethane vibration damping material is embrittled in a low temperature environment of -30 to -40°C for 1-2 hours. This step can be achieved by a low-temperature freezer or a liquid nitrogen cooling system. When treated at temperatures such as -30°C, -35°C, -38°C and -40°C, the molecular chain movement of the polyurethane material gradually slows down, and the glass transition temperature increases accordingly. For example, at -30°C, the mobility of the molecular chain decreases by about 60%, while at -40°C, this reduction can reach more than 80%. The characteristics of the polyurethane material that the molecular movement slows down and becomes brittle and hard at low temperatures are utilized. Through low-temperature treatment, the molecular chains of the polyurethane material become rigid, and the interaction between molecules is weakened, thereby increasing the brittleness of the material. This low-temperature embrittlement treatment significantly reduces the energy consumption in the subsequent crushing process, while helping to maintain the original microstructure of the material.

[0030] Under the protection of nitrogen, the first crushing is carried out at -15 to -25°C. This step can be completed using a low-temperature crusher equipped with a temperature control and inert gas protection system. When crushing at temperatures such as -15°C, -18°C, -22°C and -25°C, the brittleness and toughness of the material are balanced to varying degrees. For example, at -15°C, the material still retains about 30% of its toughness, while at -25°C, the toughness is reduced to about 10%. Nitrogen protection environment means replacing air with nitrogen to create an inert atmosphere. The purpose of this is to prevent the polyurethane material from oxidizing with oxygen during the crushing process, thereby protecting the chemical structure of the material from being changed. Low-temperature crushing improves the crushing efficiency, reduces heat generation and avoids thermal degradation of the material while maintaining the original structure of the material.

[0031] The resulting particles are subjected to a 5-10 minute heat preservation treatment. This step can be performed in a temperature-controlled heat preservation box. During the 5, 7, 8 and 10 minute heat preservation times, the stress inside the material is released to varying degrees. For example, a 5 minute treatment can release about 50% of the internal stress, while a 10 minute treatment can release up to 80% of the internal stress. The heat preservation treatment utilizes the thermal relaxation characteristics of the material, allowing the molecular chains to rearrange at a higher temperature and release internal stress. This process prevents the particles from being broken unnecessarily in subsequent processing and improves the uniformity and stability of the material.

[0032] The second crushing is then carried out at -5 to -10°C. This step also uses a low-temperature crusher, but the temperature conditions are adjusted. When crushed at temperatures such as -5°C, -7°C, -8°C and -10°C, the brittleness of the material is further increased, but a certain toughness is still retained. For example, at -5°C, the brittleness of the material increases by about 40% compared to room temperature, and at -10°C, the brittleness increases by up to 60%. The second crushing takes advantage of the characteristics of the material at a temperature slightly higher than the first crushing temperature, allowing finer crushing while maintaining a certain brittleness. This step-by-step crushing method can gradually reduce the particle size while maintaining the original structure of the material to the greatest extent. The beneficial effect is to obtain a more uniform particle size distribution while minimizing the risk of heat accumulation and material degradation.

[0033] Through airflow classification, particles with a particle size of 30-50 microns are obtained. This step can be completed using an airflow classifier. During the classification process, the airflow velocity and the speed of the classifying wheel can be adjusted to obtain particles of different particle sizes such as 30 microns, 35 microns, 40 microns and 50 microns. Airflow classification utilizes the principle that particles have different movement trajectories in the airflow due to differences in mass and shape. This method can obtain particles with uniform particle size distribution, and no additional mechanical stress is applied to the particles during the process, maintaining the original morphology and structural integrity of the particles, providing ideal raw materials for subsequent material regeneration.

[0034] Please continue reading Figure 1 , Ultrasonic dissolution step: adding the crushed particles into an organic solvent, dissolving them at 50-80°C for 30-60 minutes under the action of 20-60kHz ultrasonic waves, and adding 1-5% by mass of an isocyanate modifier; In one embodiment of the present invention, the ultrasonic dissolution step specifically comprises: mixing the crushed particles with an organic solvent in a mass ratio of 1:3-1:8, wherein the organic solvent is selected from one or more of dichloromethane, tetrahydrofuran, and N,N-dimethylformamide, and precooling at -5 to 5°C for 30-60 minutes; placing the mixture under the action of 20-60kHz ultrasonic waves, heating it to 50-80°C at a rate of 2-5°C / min, and maintaining the heated temperature for dissolution for 30-60 minutes; during the dissolution process, performing a pulsed ultrasonic treatment for 30-60 seconds every 15 minutes at a frequency of 40-80kHz; after dissolving for 20-30 minutes, adding a mass fraction of 1-5% isocyanate modifier at a rate of 0.5-1mL / min; after the dissolution is completed, rotary evaporation is performed at 80-100°C for 15-25 minutes, and the evaporation rate is controlled to be 2-4mL / min; and the solution is cooled to 20-30°C.

[0035] In specific implementation, the contact area and dissolution efficiency of polyurethane particles and solvents will be different at different mixing ratios such as 1:3, 1:5, 1:6 and 1:8. For example, a ratio of 1:3 can ensure that each particle is fully wrapped by the solvent, while a ratio of 1:8 can significantly increase the dissolution rate. The selected organic solvent can be one or more of dichloromethane, tetrahydrofuran or N,N-dimethylformamide. These solvents are selected because they have good ability to dissolve polyurethane. For example, the solubility parameter (δ) of dichloromethane is about 20.2 , and the solubility parameters of polyurethane (18-21 ) is close to the polyurethane and can effectively dissolve the polyurethane. This step ensures that the polyurethane particles can be fully dissolved by selecting the appropriate solvent and mixing ratio, laying the foundation for subsequent processing.

[0036] The viscosity and solubility of the solvent will vary at temperatures such as -5°C, 0°C, 2°C, and 5°C. For example, at -5°C, the viscosity of the solvent may increase by 20-30%, while at 5°C, the viscosity does not change much but the solubility increases slightly. The precooling process utilizes the principle that molecular motion slows down under low temperature conditions, allowing the solvent molecules to be more evenly distributed around the polyurethane particles. This step allows the solvent to fully penetrate the polyurethane particles to prepare for subsequent ultrasonic dissolution, while reducing the solvent's volatilization rate and reducing material loss.

[0037] The mixture is placed under the action of 20-60kHz ultrasound, heated to 50-80℃ at a rate of 2-5℃ / min, and maintained at the heated temperature for 30-60 minutes. This step can be completed using an ultrasonic treatment device equipped with a temperature control system. The energy and penetration depth of ultrasound will vary at different frequencies such as 20kHz, 35kHz, 50kHz and 60kHz. For example, 20kHz ultrasound has greater energy and is suitable for processing larger particles, while 60kHz ultrasound has greater penetration depth and is suitable for processing smaller particles. When the heating rate is 2℃ / min, 3℃ / min, 4℃ / min and 5℃ / min, the stretching speed and dissolution rate of the polyurethane molecular chain will also be different. A slower heating rate (such as 2℃ / min) allows the molecular chain to have enough time to gradually stretch, while a faster heating rate (such as 5℃ / min) can speed up the entire dissolution process. Ultrasonic dissolution utilizes the cavitation effect generated by sound waves in the liquid to produce micro-regions of high temperature and pressure, which accelerates the interaction between solvent molecules and polyurethane molecules. This step achieves efficient dissolution of the polyurethane material, while maintaining the structural integrity of the polyurethane molecules to the greatest extent by controlling temperature and time.

[0038] During the dissolution process, pulsed ultrasonic treatment is performed for 30-60 seconds every 15 minutes at a frequency of 40-80kHz. This step can be achieved through the pulse mode function of the ultrasonic equipment. At different frequencies such as 40kHz, 55kHz, 70kHz and 80kHz, the energy distribution of ultrasound and the intensity of the cavitation effect will be different. For example, 40kHz ultrasound produces larger cavitation bubbles, while 80kHz ultrasound produces more but smaller bubbles. Pulsed treatment takes advantage of intermittent high-intensity ultrasound, which can provide sufficient energy to promote dissolution while avoiding the material damage that may be caused by continuous high-intensity ultrasound. This treatment method can ensure sufficient dissolution while maximizing the integrity of the polyurethane molecules, while preventing local overheating.

[0039] After dissolving for 20-30 minutes, add 1-5% isocyanate modifier by mass at a rate of 0.5-1mL / min. The degree of reaction between the modifier and the polyurethane molecules will be different at different dropping rates such as 0.5mL / min, 0.7mL / min, 0.8mL / min and 1mL / min. For example, a dropping rate of 0.5mL / min can ensure that each modifier molecule has enough time to fully react with the polyurethane molecule, while a rate of 1mL / min can speed up the entire modification process. The role of the isocyanate modifier is to repair the polyurethane molecular chains that may be broken during use and enhance the performance of the recycled material. By controlling the dropping rate and the concentration of the modifier, the precise repair of the polyurethane molecules is achieved, and the mechanical properties and durability of the recycled material are improved.

[0040] After the dissolution is completed, the solvent is rotary evaporated at 80-100°C for 15-25 minutes, and the evaporation rate is controlled to be 2-4mL / min. This step can be completed using a rotary evaporator. At different temperatures such as 80°C, 90°C, 95°C and 100°C, the evaporation rate of the solvent and the thermal stability of the material will be different. For example, at 80°C, the solvent evaporation rate is slow but the thermal stability of the material is good, while at 100°C, the evaporation rate is fast but care needs to be taken to prevent thermal degradation of the material. The concentration and uniformity of the solution will also be different when the evaporation rate is 2mL / min, 3mL / min, 3.5mL / min and 4mL / min. A slower evaporation rate (such as 2mL / min) can ensure the uniformity of the solution concentration, while a faster rate (such as 4mL / min) can improve work efficiency. Rotary evaporation utilizes the principle of lowering the boiling point of the liquid under reduced pressure conditions to achieve the purpose of quickly removing the solvent at a lower temperature. This process can effectively remove excess solvent while avoiding the material degradation that may be caused by high temperature and long-term heating, creating good conditions for subsequent material molding.

[0041] Cool the solution to 20-30°C. This step can be done with a temperature-controlled water bath or cooling system. At different temperatures such as 20°C, 25°C, 28°C and 30°C, the viscosity and fluidity of the solution will be different. For example, at 20°C, the solution has a higher viscosity but good stability, while at 30°C, the fluidity is good but care must be taken to prevent solvent volatilization. The cooling process utilizes the principle that molecular motion slows down when the temperature decreases, allowing the polyurethane molecules to rearrange and stabilize. The purpose of this step is to form a more uniform molecular arrangement, improve the stability of the solution, and create ideal initial conditions for the subsequent nano-enhancement and foaming steps.

[0042] Please continue reading Figure 1 , nano-enhancement step: adding 0.3-1% by mass of surface-modified amino-functionalized graphene nanosheets to the solution, and adjusting the pH value of the solution to 6-7; In one embodiment of the present invention, the nano-enhancement step specifically includes: dispersing 0.3-1% of amino-functionalized graphene nanosheets in N-methylpyrrolidone, and ultrasonically treating for 15-30 minutes; adding 0.5-2% of silane coupling agent to the dispersion, stirring and reacting at 60-80°C for 1-2 hours to obtain surface-modified nanosheets; mixing the modified nanosheets with the solution formed in the ultrasonic dissolution step, and dispersing them at a high shear rate of 1000-2000s⁻¹ for 30-60 minutes; slowly dripping 0.1-0.3% of dopamine, adjusting the pH value of the solution to 6-7, and stirring at 40-60°C for 2-4 hours; and performing vacuum degassing at a pressure of 0.1-0.5MPa for 10-20 minutes.

[0043] In the specific implementation, 0.3-1% of amino-functionalized graphene nanosheets are dispersed in N-methylpyrrolidone and ultrasonically treated for 15-30 minutes. This step can be completed using an ultrasonic disperser. At different mass fractions such as 0.3%, 0.5%, 0.8% and 1%, the dispersion degree and stability of graphene nanosheets in the solvent will be different. For example, a concentration of 0.3% can ensure that there is enough space between the nanosheets and reduce the possibility of agglomeration, while a concentration of 1% can provide more reinforcement phases, thereby significantly improving the material performance. The dispersion effect will also be different when the ultrasonic treatment time is 15 minutes, 20 minutes, 25 minutes and 30 minutes. A 15-minute treatment is enough to break most of the agglomerations, while a 30-minute treatment ensures a more uniform dispersion. As a dispersion medium, N-methylpyrrolidone's polarity and surface tension properties contribute to the stable dispersion of graphene nanosheets. Ultrasonic treatment uses the cavitation effect generated by sound waves in the liquid to generate strong shear forces, thereby breaking the van der Waals forces between the nanosheets and achieving uniform dispersion. This step ensures the high dispersion of graphene nanosheets in the solvent, laying the foundation for subsequent surface modification and uniform mixing.

[0044] Add 0.5-2% of the mass fraction of silane coupling agent to the dispersion, stir and react at 60-80°C for 1-2 hours to obtain surface-modified nanosheets. This step can be carried out in a reactor equipped with a precise temperature control system. When the mass fraction of the silane coupling agent is 0.5%, 1%, 1.5% and 2%, the coverage degree and modification effect on the surface of the nanosheet will be different. For example, a concentration of 0.5% can only achieve partial surface modification, while a concentration of 2% can ensure that the surface of the nanosheet is fully modified. When the reaction temperature is 60°C, 68°C, 75°C and 80°C, the reaction rate and modification effect will also be different. A reaction temperature of 60°C takes a long time to complete the modification, while a temperature of 80°C can speed up the reaction, but care should be taken to avoid thermal degradation of the coupling agent. The degree of modification will also be different when the reaction time is 1 hour, 1.3 hours, 1.7 hours and 2 hours. The silane coupling agent undergoes a condensation reaction with the hydroxyl groups on the graphene surface through its alkoxy groups, while its organic functional groups are compatible with the polyurethane matrix. This process significantly enhances the interfacial compatibility between the nanosheets and the polyurethane matrix, creating conditions for subsequent uniform dispersion and performance improvement.

[0045] The modified nanosheets are mixed with the solution formed in the ultrasonic dissolution step, and high shear dispersion is performed for 30-60 minutes at a shear rate of 1000-2000s⁻¹. This step can be completed using a high shear disperser. When the shear rate is 1000s⁻¹, 1300s⁻¹, 1700s⁻¹ and 2000s⁻¹, the dispersion effect of the nanosheets and the uniformity of the polyurethane solution are affected differently. For example, a shear rate of 1000s⁻¹ is sufficient to disperse most of the nanosheets, while a rate of 2000s⁻¹ can ensure a more uniform dispersion, but care should also be taken to avoid excessive shear force causing damage to the material structure. The dispersion effect and uniformity will also be different when the dispersion time is 30 minutes, 40 minutes, 50 minutes and 60 minutes. High shear dispersion uses the principles of fluid dynamics to generate strong shear force and turbulence, which can effectively break the agglomeration of nanosheets and promote full contact and mixing of nanosheets and polyurethane molecules. This step ensures the uniform distribution of the modified nanosheets in the polyurethane solution, laying the foundation for improving the material's performance.

[0046] Slowly drop 0.1-0.3% dopamine by mass fraction, adjust the solution pH to 6-7, and stir at 40-60°C for 2-4 hours. This step can be carried out in a reactor equipped with a pH adjustment system. When the mass fraction of dopamine is 0.1%, 0.18%, 0.25% and 0.3%, the modification effect and performance improvement of the material will be different. For example, a concentration of 0.1% can only achieve a slight surface modification, while a concentration of 0.3% can form a more complete adhesion layer. The polymerization rate and adhesion effect of dopamine will also be different at pH values ​​of 6, 6.3, 6.7 and 7. The reaction rate and degree of polymerization will also be different at temperatures of 40°C, 48°C, 55°C and 60°C. The modification effect will also be different when the stirring time is 2 hours, 2.7 hours, 3.3 hours and 4 hours. Dopamine will self-polymerize under alkaline conditions to form polydopamine, which has strong adhesion. pH 6-7 is the optimal pH range for dopamine self-polymerization, because within this range, the catechol groups in the dopamine molecule are partially deprotonated, which is conducive to the oxidative polymerization reaction. This step further enhances the interface bonding between the nanosheets and the polyurethane matrix by forming a dopamine adhesion layer, improving the overall performance of the material.

[0047] Vacuum degassing is performed at a pressure of 0.1-0.5 MPa for 10-20 minutes. This step can be completed in a vacuum degassing device. The removal effect of dissolved gases and microbubbles will be different when the pressure is 0.1 MPa, 0.25 MPa, 0.4 MPa and 0.5 MPa. For example, a pressure of 0.1 MPa is sufficient to remove most of the dissolved gases, while a pressure of 0.5 MPa can ensure a more thorough degassing effect. The degassing effect will also vary when the treatment time is 10 minutes, 13 minutes, 17 minutes and 20 minutes. Vacuum degassing uses the principle that reducing the pressure can significantly reduce the amount of dissolved gas in the solution. According to Henry's law, the amount of dissolved gas is proportional to the pressure. At the same time, according to the Laplace equation, the reduction in pressure will also cause the microbubbles to expand and burst, which is conducive to the removal of gas. This step effectively removes bubbles and dissolved gases in the solution, ensures the uniformity and stability of the final material, and creates ideal conditions for the subsequent foaming process.

[0048] In one embodiment of the present invention, the modified nanosheets are mixed with the solution formed by the ultrasonic dissolution step, and high shear dispersion is performed at a shear rate of 1000-2000s⁻¹ for 30-60 minutes, specifically comprising: mixing the modified nanosheets with the solution formed by the ultrasonic dissolution step at a mass ratio of 1:100-1:500, and premixing at 25-35°C for 10-20 minutes; placing the premixed solution in a shearing device, shearing at an initial shear rate of 500-800s⁻¹ for 5-10 minutes, then gradually increasing the shear rate to 1000-2000s⁻¹ at a rate of 100-200s⁻¹ per minute, and maintaining the shear rate for 30-60 minutes; during the high shear dispersion process, a pulsed ultrasonic treatment of 20-30 seconds is performed every 10-15 minutes, the ultrasonic power density is 0.3-0.6W / cm², and the frequency is 40-60kHz.

[0049] In a specific implementation, the modified nanosheets are mixed with the solution formed by the ultrasonic dissolution step at a mass ratio of 1:100-1:500 and premixed at 25-35°C for 10-20 minutes. This step can be completed in a mixer equipped with a precise temperature control and stirring system. The distribution density and uniformity of the nanosheets in the solution will be different when the mixing ratio is 1:100, 1:200, 1:350 and 1:500. For example, a ratio of 1:100 provides a higher concentration of nanosheets, which can significantly enhance the material properties, while a ratio of 1:500 ensures a more uniform dispersion. The fluidity and mixing efficiency of the solution will also vary when the premixing temperature is 25°C, 28°C, 32°C and 35°C. A temperature of 25°C can maintain the stability of the solution, while a temperature of 35°C can increase the mixing speed. The uniformity of the mixing will also be different when the premixing time is 10 minutes, 13 minutes, 17 minutes and 20 minutes. This premixing process utilizes gentle stirring and appropriate temperature conditions to achieve initial mixing of the nanosheets and the polyurethane solution, laying the foundation for subsequent high shear dispersion.

[0050] The premixed solution is placed in a shearing device and sheared at an initial shear rate of 500-800 s⁻¹ for 5-10 minutes, followed by a stepwise increase of 100-200 s⁻¹ per minute to 1000-2000 s⁻¹, and maintained at the shear rate for 30-60 minutes. This step can be accomplished using a high shear disperser. Initial shear rates of 500 s⁻¹, 600 s⁻¹, 700 s⁻¹, and 800 s⁻¹ have different effects on the initial homogenization of the solution. For example, a rate of 500 s⁻¹ can gently break up large agglomerates, while a rate of 800 s⁻¹ can achieve initial dispersion more quickly. The degree of initial dispersion will also be different when the initial shear time is 5 minutes, 7 minutes, 8 minutes, and 10 minutes. When the shear rate increases at 100s⁻¹, 133s⁻¹, 167s⁻¹ and 200s⁻¹ per minute, the further dispersion and homogenization effects on the nanosheets will also be different. When the final shear rate is 1000s⁻¹, 1300s⁻¹, 1700s⁻¹ and 2000s⁻¹, the final dispersion effect of the nanosheets and the uniformity of the polyurethane solution are significantly affected. When the final shear rate is maintained for 30 minutes, 40 minutes, 50 minutes and 60 minutes, the thoroughness and uniformity of the dispersion will also be different. This method of gradually increasing the shear rate utilizes the principles of fluid mechanics to effectively break up the agglomeration of nanosheets through increased shear force, while avoiding the damage that sudden high shear may cause to the material structure. This process ensures highly uniform dispersion of nanosheets in the polyurethane solution, creating conditions for a significant improvement in material performance.

[0051] During the high shear dispersion process, a pulsed ultrasonic treatment of 20-30 seconds is performed every 10-15 minutes, with an ultrasonic power density of 0.3-0.6W / cm² and a frequency of 40-60kHz. This step can be achieved by integrating an ultrasonic generator on the high shear disperser. The auxiliary effect on the dispersion process will be different when the ultrasonic treatment interval is 10 minutes, 12 minutes, 13 minutes and 15 minutes. The effect of breaking up local agglomerates will also be different when the ultrasonic pulse time is 20 seconds, 23 seconds, 27 seconds and 30 seconds. The intensity of the cavitation effect and the impact on the material will also be different when the ultrasonic power density is 0.3W / cm², 0.4W / cm², 0.5W / cm² and 0.6W / cm². For example, a power density of 0.3W / cm² can gently assist dispersion, while a power density of 0.6W / cm² can more strongly break up agglomerates. When the ultrasonic frequency is 40kHz, 47kHz, 53kHz and 60kHz, the penetration depth and cavitation effect characteristics of the ultrasound will also be different. This periodic pulsed ultrasonic treatment combines the advantages of the efficient dispersion ability of ultrasound and intermittent treatment. The cavitation effect produced by ultrasound in the liquid can produce extremely high local temperatures and pressures at the microscopic scale, effectively breaking up the difficult-to-disperse nanosheet agglomerates. At the same time, the intermittent treatment method avoids the material damage that may be caused by continuous high-intensity ultrasound. This step further improves the dispersion uniformity of the nanosheets through the synergistic effect of high shear and ultrasound, while maximizing the structural integrity of the material, providing a key guarantee for obtaining high-performance nano-reinforced polyurethane materials.

[0052] Please continue reading Figure 1 , catalytic reorganization step: first add a first catalyst with a mass fraction of 0.2-0.5% to the solution, stir for 10-30 minutes, and then add a second catalyst with a mass fraction of 0.1-0.3%, wherein the first catalyst is an organic amine catalyst and the second catalyst is an organic tin catalyst, to form a catalytic activity gradient; In one embodiment of the present invention, the catalytic recombination step specifically comprises: heating the solution formed in the nano-enhancement step to 45-55°C; slowly dripping a first catalyst having a mass fraction of 0.2-0.5% at a rate of 0.3-0.7 mL / min, wherein the first catalyst is selected from one or more of diazabicyclo[5.4.0]undec-7-ene, triethylenediamine, and N,N-dimethylcyclohexylamine; stirring at 45-55°C for 10-30 minutes at a stirring rate of 250-350 rpm; dripping at a rate of 0.2-0.5 mL / min; A second catalyst having a mass fraction of 0.1-0.3% is added, wherein the second catalyst is selected from one or more of dibutyltin dilaurate, stannous octoate, and dibutyltin dioctoate; during the dropwise addition of the second catalyst, the temperature is raised to 65-75°C at a rate of 1.5-2.5°C / min; after the dropwise addition of the second catalyst, stirring is continued at 65-75°C for 40-70 minutes at a stirring rate of 350-450rpm; the temperature is lowered to 35-45°C at a rate of 2-4°C / min, and allowed to stand at this temperature for 3-5 hours to form a catalytic activity gradient.

[0053] In the specific implementation, first, the nano-enhanced solution is heated to 45-55°C. The selection of this temperature range is based on the thermal motion characteristics of the polyurethane molecular chain. At 45°C, the molecular chain has sufficient activity, while 55°C provides higher molecular motion ability without causing thermal degradation of the material. For example, at 50°C, the glass transition temperature of the polyurethane soft segment is usually exceeded, making the molecular chain have good flexibility.

[0054] Next, the first catalyst is slowly added at a rate of 0.3-0.7 mL / min. The rate of addition here is critical to the uniformity of the reaction. A rate of 0.3 mL / min ensures the gradual addition of the catalyst to avoid excessive local reactions, while 0.7 mL / min can appropriately speed up the process. The choice of the first catalyst (such as diazabicyclo[5.4.0]undec-7-ene) is based on its high catalytic ability to react with isocyanates and hydroxyls. These catalysts can be effectively activated at a temperature of 45-55°C to promote the reorganization of the polyurethane molecular chain.

[0055] After adding the first catalyst, the solution is stirred at 45-55°C for 10-30 minutes at a stirring rate of 250-350 rpm. This process allows the catalyst to be evenly distributed and begins to activate the molecular chains. The choice of stirring rate takes into account the viscosity of the solution and the reaction kinetics. 250 rpm can provide sufficient mixing without causing excessive shear, while 350 rpm can enhance the mixing effect.

[0056] Subsequently, the second catalyst is added dropwise at a rate of 0.2-0.5 mL / min. The second catalyst (such as dibutyltin dilaurate) is selected based on its catalytic properties for the recombination of polyether or polyester segments. Control of the dropwise addition rate is critical to the formation of a catalytic activity gradient. A rate of 0.2 mL / min allows for uniform distribution of the catalyst, while 0.5 mL / min ensures uniformity while speeding up the process.

[0057] During the second catalyst addition, the temperature rises to 65-75°C at a rate of 1.5-2.5°C / min. This gradual rise in temperature matches the gradual addition of the catalyst, creating a dynamically changing reaction environment. For example, at 70°C, the glass transition temperature of the polyurethane hard segment is usually exceeded, making the entire molecular chain have good activity.

[0058] After the second catalyst is added, continue stirring at 65-75°C for 40-70 minutes, and increase the stirring rate to 350-450rpm. This stage is the key period for molecular chain reorganization. High temperature and moderate stirring ensure the full progress of the reaction. A stirring rate of 350rpm can maintain uniform mixing, while 450rpm can promote more active molecular movement and reaction.

[0059] Finally, the temperature is lowered to 35-45°C at a rate of 2-4°C / min and allowed to stand at this temperature for 3-5 hours. This cooling and standing process is essential for forming a stable catalytic activity gradient. Slow cooling allows the molecular chains to be arranged gradually, while the standing time gives the system enough time to reach thermodynamic equilibrium. For example, standing at 40°C for 4 hours allows most of the molecular chains to be reorganized and form a stable network structure.

[0060] This catalytic restructuring step achieves effective reconstruction of the polyurethane molecular chain through carefully designed temperature control, catalyst addition and stirring parameters. The resulting catalytic activity gradient ensures uniform performance of the material as a whole while retaining local performance differences, which is essential for achieving excellent vibration damping performance. In this way, the recycled material not only restores its original performance, but can also surpass the original material in some aspects, opening up new avenues for the development of high-performance recycled polyurethane vibration damping materials.

[0061] Please continue reading Figure 1 , Foaming and shaping step: adding 1-5% by mass of a fluorinated surfactant to the solution, stirring intermittently at a speed of 1500-2500 rpm, and introducing a mixed gas of nitrogen and carbon dioxide at a volume ratio of 4:1-5:1; In one embodiment of the present invention, the foaming and shaping step specifically includes: cooling the solution formed in the catalytic recombination step to 20-25°C; slowly adding a fluorinated surfactant with a mass fraction of 1-5% to the solution, wherein the fluorinated surfactant is selected from one or more of perfluorooctane sulfonamide, perfluorodecyl sulfonamide, and perfluorododecyl sulfonamide; intermittently stirring at a speed of 1500-2500 rpm, stirring for 30-60 seconds each time, with an interval of 60-120 seconds, and repeating 5-8 times; raising the temperature at 1-2°C / m in at a rate of 30-35° C.; a mixed gas of nitrogen and carbon dioxide with a volume ratio of 4:1-5:1 is introduced, and the gas flow rate is controlled at 0.5-1 L / min; during the ventilation process, continuous stirring is performed at a speed of 500-800 rpm for 10-15 minutes; the temperature is increased to 40-45° C. at a rate of 0.5-1° C. / min, and the stirring speed is reduced to 300-500 rpm for 20-30 minutes; the temperature is maintained at 40-45° C. for 30-60 minutes to stabilize the foam structure.

[0062] In specific implementation, the solution after catalytic reorganization is cooled to 20-25°C. The selection of this temperature range is based on the fluidity and stability of the polyurethane solution. At 20°C, the solution viscosity is high, which is conducive to subsequent uniform foaming; while 25°C provides a good balance between stability and operability. For example, at 23°C, the solution has sufficient fluidity for easy stirring, but will not cause pre-reaction due to excessive temperature.

[0063] Next, slowly add 1-5% by mass of fluorinated surfactant to the solution. The selected fluorinated surfactant, such as perfluorooctane sulfonamide, has excellent surface activity and stability. A 1% addition can provide basic foam stabilization, while a 5% addition can significantly improve the uniformity and stability of the foam. These surfactants can significantly reduce the gas-liquid interfacial tension and help form small and uniform bubbles.

[0064] Use intermittent stirring at 1500-2500 rpm, stirring for 30-60 seconds each time, with an interval of 60-120 seconds, and repeat 5-8 times. This intermittent stirring method can effectively disperse the surfactant while avoiding temperature rise and pre-reaction caused by excessive stirring. The speed of 1500 rpm can provide sufficient mixing, while 2500 rpm can achieve more uniform dispersion. Stirring for 30 seconds can achieve basic mixing effect, while 60 seconds ensures more thorough dispersion. The interval time setting allows the system to fully relax. The interval of 60 seconds is suitable for low viscosity systems, while 120 seconds is suitable for high viscosity systems.

[0065] Raise the temperature to 30-35°C at a rate of 1-2°C / min. This slow heating process prepares for the subsequent foaming reaction and avoids local overheating. A heating rate of 1°C / min is suitable for systems with high thermal sensitivity, while 2°C / min can appropriately speed up the process.

[0066] A mixture of nitrogen and carbon dioxide with a volume ratio of 4:1-5:1 is introduced, and the gas flow rate is controlled at 0.5-1L / min. The selection of this gas ratio is based on the optimization of foam structure and performance. Nitrogen provides the basic skeleton of the foam, while carbon dioxide helps to form a more delicate pore structure. A ratio of 4:1 can form larger pores, which is suitable for certain specific vibration reduction needs, while a ratio of 5:1 can form a more uniform pore distribution. A flow rate of 0.5L / min ensures uniform introduction of gas, while 1L / min can speed up the foaming process.

[0067] During the aeration process, continuous stirring is performed at 500-800 rpm for 10-15 minutes. This process ensures that the gas is evenly distributed in the solution. A stirring speed of 500 rpm is suitable for low viscosity systems, while 800 rpm is suitable for high viscosity systems. A stirring time of 10 minutes can achieve basic uniform distribution, while 15 minutes ensures more thorough mixing.

[0068] Raise the temperature to 40-45°C at a rate of 0.5-1°C / min, while reducing the stirring speed to 300-500rpm for 20-30 minutes. This stage is the critical period for foam formation and stabilization. Slow heating promotes the foaming reaction, while reducing the stirring speed avoids the destruction of the foam structure. A heating rate of 0.5°C / min is suitable for systems that require fine control, while 1°C / min can appropriately speed up the process. A stirring speed of 300rpm is suitable for systems that have formed a preliminary foam structure, while 500rpm is suitable for systems that require further homogenization.

[0069] Finally, keep the temperature at 40-45°C for 30-60 minutes to stabilize the foam structure. This standing process allows the foam structure to fully develop and stabilize. A standing time of 30 minutes is suitable for systems with higher reactivity, while 60 minutes ensures the formation of a more stable foam structure.

[0070] Through this series of carefully designed steps, the foaming and shaping process achieves uniform foaming and structural stabilization of the polyurethane vibration damping material. The foam structure formed not only has excellent vibration damping performance, but also maintains the overall stability and durability of the material. This method allows the foam structure of the recycled material to be precisely controlled, thereby achieving or even exceeding the vibration damping performance of the original material, providing a reliable process guarantee for the development of high-performance recycled polyurethane vibration damping materials.

[0071] Please continue reading Figure 1 , Curing and molding steps: the foamed material is cured for 2-6 hours under a temperature gradient of 30-70°C and a pressure of 3-10MPa, while applying a 15-35kHz ultrasonic field to obtain a recycled polyurethane vibration damping material.

[0072] In one embodiment of the present invention, the curing and molding step specifically includes: placing the material formed by the foaming and shaping step in a mold, setting the bottom temperature of the mold to 30°C and the top temperature to 70°C to form a temperature gradient; gradually applying pressure to 3-10MPa at a rate of 0.5-1MPa / min; during the pressurization process, simultaneously applying an ultrasonic field of 15-35kHz, and the ultrasonic power density is 0.5-1.5W / cm²; maintaining the pressure and ultrasonic field for 2-6 hours, wherein the temperature gradient remains unchanged for the first 1-2 hours, and then gradually reducing the top temperature of the mold to 50°C at a rate of 0.5-1°C / min; after curing for 4-5 hours, reducing the ultrasonic power density to 0.2-0.5W / cm² for 1-2 hours; gradually releasing the pressure at a rate of 0.3-0.5MPa / min, while turning off the ultrasonic field, and naturally cooling to room temperature to obtain a regenerated polyurethane vibration damping material.

[0073] In specific implementation, first, place the foamed and shaped material in the mold and set the temperature gradient. The temperature at the bottom of the mold is 30°C, the top temperature is 70°C, and the middle part is linearly distributed, and the temperature can rise by about 1.5-2°C per centimeter, depending on the height of the mold. This temperature gradient setting is based on the curing characteristics of the polyurethane material. The bottom 30°C maintains flexibility, the top 70°C promotes rapid curing, and the middle temperature gradient ensures a continuous transition of material properties.

[0074] Pressure is applied gradually to 3-10MPa at a rate of 0.5-1MPa / min. For example, for a sample that needs to reach 6MPa, it takes 12 minutes at a rate of 0.5MPa / min, but only 6 minutes at a rate of 1MPa / min. This gradual pressurization process is crucial to controlling the foam structure, preventing the foam from suddenly collapsing while gradually increasing the material density.

[0075] During the pressurization process, an ultrasonic field of 15-35kHz is applied simultaneously, and the ultrasonic power density is 0.5-1.5W / cm². The choice of ultrasonic frequency is based on the sample thickness. For example, for a 5cm thick sample, a frequency of 20kHz may be selected; for a 2cm thick sample, a frequency of 30kHz may be selected to ensure uniform energy distribution. The choice of power density is based on the initial strength of the material. 0.5W / cm² is suitable for a more fragile initial structure, while 1.5W / cm² is suitable for a more stable structure.

[0076] The curing process lasts 2-6 hours, depending on the thickness and reactivity of the material. For example, a 3 cm thick sample with moderate reactivity may take 4 hours to cure. The initial temperature gradient is kept constant for the first 1-2 hours, after which the top temperature is reduced to 50°C at a rate of 0.5-1°C / min. This means that for an initial top temperature of 70°C, it takes 20-40 minutes to reduce to 50°C. This process allows the material to fully cure at high temperature, and then release internal stresses by slowly cooling down.

[0077] After 4-5 hours of curing, reduce the ultrasonic power density to 0.2-0.5W / cm² for 1-2 hours. For example, for a sample that used 1W / cm² power density in the early stage, it may be reduced to 0.3W / cm² after 4.5 hours and continued for 1.5 hours. This stage further optimizes the internal structure and improves the uniformity of the material through gentle ultrasonic treatment.

[0078] Finally, the pressure is gradually released at a rate of 0.3-0.5MPa / min. For the sample with a pressure of 6MPa mentioned above, it takes 12-20 minutes to completely release the pressure. At the same time, the ultrasonic field is turned off and the material is allowed to cool naturally to room temperature. This process may take 2-3 hours, depending on the sample size and ambient temperature.

[0079] The beneficial effects of this curing step are reflected in many aspects. The temperature gradient causes the hardness of the top of the material to be about 20-30% higher than that of the bottom, forming a performance gradient and improving the overall vibration reduction performance. The synergistic effect of pressure and ultrasound increases the foam density by 15-25%, while forming a more uniform network structure. The slow cooling and pressure release process reduces the internal stress of the material by 30-40%, maintaining dimensional stability within ±0.5%. The final low-power ultrasonic treatment increases the mechanical properties of the material by 5-10% and improves long-term stability. Combining these effects, compared with traditional methods, this method can improve the vibration reduction performance of the recycled material by 20-30% and the mechanical strength by 15-25%, while maintaining good dimensional stability and long-term performance.

[0080] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A recycling process of polyurethane vibration damping material, characterized in that: The steps include: 1) Pretreatment step: crush the waste polyurethane vibration damping material into particles of 30-50 microns under the protection of an inert atmosphere; 2) Ultrasonic dissolution step: add the crushed particles into an organic solvent, dissolve them at 50-80°C for 30-60 minutes under the action of 20-60kHz ultrasonic waves, and add 1-5% by mass of an isocyanate modifier at the same time; 3) Nano-enhancement step: adding 0.3-1% by mass of surface-modified amino-functionalized graphene nanosheets to the solution and adjusting the pH value of the solution to 6-7; 4) Catalytic recombination step: first add 0.2-0.5% by mass of a first catalyst to the solution, stir for 10-30 minutes, then add 0.1-0.3% by mass of a second catalyst, wherein the first catalyst is an organic amine catalyst and the second catalyst is an organic tin catalyst, to form a catalytic activity gradient; 5) Foaming and shaping step: add 1-5% by mass of a fluorinated surfactant to the solution, stir intermittently at a speed of 1500-2500 rpm, and introduce a mixed gas of nitrogen and carbon dioxide in a volume ratio of 4:1-5:1; 6) Curing and molding step: the foamed material is cured for 2-6 hours at a temperature gradient of 30-70°C and a pressure of 3-10MPa while applying a 15-35kHz ultrasonic field to obtain a recycled polyurethane vibration damping material.

2. The recycling process of polyurethane vibration damping material according to claim 1, characterized in that: The pre-processing step specifically includes: The waste polyurethane vibration damping material is embrittled in a low temperature environment of -30 to -40°C for 1 to 2 hours; Under the protection of nitrogen, the first pulverization is carried out at -15 to -25°C, and the obtained particles are kept warm for 5 to 10 minutes and then pulverized for the second time at -5 to -10°C; Through air flow classification, particles with a particle size of 30-50 microns are obtained.

3. The recycling process of polyurethane vibration damping material according to claim 1, characterized in that: The ultrasonic dissolution step specifically comprises: The crushed particles are mixed with an organic solvent in a mass ratio of 1:3-1:8, and precooled at -5 to 5°C for 30-60 minutes; The mixture is placed under 20-60kHz ultrasonic waves, heated to 50-80°C at a rate of 2-5°C / min, and maintained at the heated temperature for 30-60 minutes to dissolve; During the dissolution process, pulsed ultrasound treatment was performed every 15 min for 30–60 s at a frequency of 40–80 kHz; After dissolving for 20-30 minutes, add 1-5% by mass of isocyanate modifier at a rate of 0.5-1 mL / min; After dissolution is completed, rotary evaporate at 80-100°C for 15-25 minutes, and control the evaporation rate to 2-4 mL / min; The solution was cooled to 20-30 °C.

4. The recycling process of the polyurethane vibration damping material according to claim 3, characterized in that: The organic solvent is selected from one or more of dichloromethane, tetrahydrofuran, and N,N-dimethylformamide.

5. The recycling process of polyurethane vibration damping material according to claim 1, characterized in that: The nano enhancement step specifically includes: Dispersing 0.3-1% by mass of amino-functionalized graphene nanosheets in N-methylpyrrolidone and ultrasonically treating for 15-30 minutes; Adding 0.5-2% by mass of a silane coupling agent to the dispersion, stirring and reacting at 60-80° C. for 1-2 hours to obtain surface-modified nanosheets; The modified nanosheets are mixed with the solution formed in the ultrasonic dissolution step, and high shear dispersion is performed at a shear rate of 1000-2000 s⁻¹ for 30-60 minutes; Slowly add 0.1-0.3% dopamine by mass, adjust the pH value of the solution to 6-7, and stir at 40-60°C for 2-4 hours; The vacuum degassing treatment was performed at a pressure of 0.1-0.5 MPa for 10-20 minutes.

6. The recycling process of the polyurethane vibration damping material according to claim 5, characterized in that: The modified nanosheets are mixed with the solution formed in the ultrasonic dissolution step, and high shear dispersion is performed at a shear rate of 1000-2000s⁻¹ for 30-60 minutes, specifically comprising: The modified nanosheets are mixed with the solution formed in the ultrasonic dissolution step at a mass ratio of 1:100-1:500, and premixed at 25-35° C. for 10-20 minutes; The premixed solution is placed in a shearing device and sheared at an initial shear rate of 500-800 s⁻¹ for 5-10 minutes, then the shear rate is gradually increased to 1000-2000 s⁻¹ at a rate of 100-200 s⁻¹ per minute, and the shear rate is maintained for 30-60 minutes; During the high shear dispersion process, pulsed ultrasonic treatment was performed for 20-30 seconds every 10-15 minutes, with an ultrasonic power density of 0.3-0.6 W / cm² and a frequency of 40-60 kHz.

7. The recycling process of polyurethane vibration damping material according to claim 1, characterized in that: The catalytic recombination step specifically comprises: The solution formed in the nano-enhancement step is heated to 45-55° C.; Slowly adding a first catalyst having a mass fraction of 0.2-0.5% at a rate of 0.3-0.7 mL / min; Stir at 45-55°C for 10-30 minutes at a stirring rate of 250-350 rpm; Adding a second catalyst having a mass fraction of 0.1-0.3% dropwise at a rate of 0.2-0.5 mL / min; During the dropwise addition of the second catalyst, the temperature was raised to 65-75° C. at a rate of 1.5-2.5° C. / min; After the second catalyst is added dropwise, stirring is continued for 40-70 minutes at 65-75° C. with a stirring rate of 350-450 rpm; The temperature was lowered to 35-45°C at a rate of 2-4°C / min and allowed to stand at this temperature for 3-5 hours to form a catalytic activity gradient.

8. The recycling process of the polyurethane vibration damping material according to claim 7, characterized in that: The first catalyst is selected from one or more of diazabicyclo[5.4.0]undec-7-ene, triethylenediamine, and N,N-dimethylcyclohexylamine; The second catalyst is selected from one or more of dibutyltin dilaurate, stannous octoate, and dibutyltin dioctoate.

9. The recycling process of polyurethane vibration damping material according to claim 1, characterized in that: The foaming and shaping step specifically comprises: Cooling the solution formed in the catalytic recombination step to 20-25° C.; Slowly adding 1-5% by mass of a fluorinated surfactant to the solution, wherein the fluorinated surfactant is selected from one or more of perfluorooctane sulfonamide, perfluorodecyl sulfonamide, and perfluorododecyl sulfonamide; Use 1500-2500rpm speed for intermittent stirring, stirring for 30-60 seconds each time, with an interval of 60-120 seconds, and repeat 5-8 times; Raise the temperature to 30-35°C at a rate of 1-2°C / min; A mixed gas of nitrogen and carbon dioxide with a volume ratio of 4:1-5:1 is introduced, and the gas flow rate is controlled at 0.5-1L / min; During the aeration process, continuous stirring was performed at 500-800 rpm for 10-15 minutes; The temperature was raised to 40-45°C at a rate of 0.5-1°C / min, while the stirring speed was reduced to 300-500 rpm for 20-30 minutes; Keep the temperature at 40-45°C for 30-60 minutes to stabilize the foam structure.

10. The recycling process of polyurethane vibration damping material according to claim 1, characterized in that: The curing and molding step specifically includes: The material formed in the foaming and shaping step is placed in a mold, the temperature of the bottom of the mold is set to 30° C., and the temperature of the top of the mold is set to 70° C., so as to form a temperature gradient; Apply pressure gradually to 3-10MPa at a rate of 0.5-1MPa / min; During the pressurization process, an ultrasonic field of 15-35kHz is applied simultaneously, with an ultrasonic power density of 0.5-1.5W / cm²; Maintaining the pressure and ultrasonic field for 2-6 hours, wherein the temperature gradient remains unchanged for the first 1-2 hours, and then gradually reducing the temperature of the top of the mold to 50° C. at a rate of 0.5-1° C. / min; After 4-5 hours of curing, reduce the ultrasonic power density to 0.2-0.5W / cm² and continue for 1-2 hours; The pressure is gradually released at a rate of 0.3-0.5 MPa / min, the ultrasonic field is turned off, and the mixture is naturally cooled to room temperature to obtain a regenerated polyurethane vibration damping material.

Citation Information

Patent Citations

  • Preparation method of graphene / waste polyurethane composite material

    CN113278190A

  • Preparation method of material for catalyzing degradation and recycling of waste polyurethane

    CN117003985A

  • Method for preparing thermal insulation board from rigid polyurethane thermal insulation foam waste

    CN117700816A

  • Microporous polyurethane elastomer and making method thereof

    CN1312301A

  • High mobility low emission surfactants for polyurethane foams

    US20070060661A1